Soundness Level of the Regional Development Banks Using REGC Method During COVID – 19 Pandemic - Irvandi W. Ombuh; Jones X. Pontoh (AIBPM Publisher, 2022)
The COVID-19 Pandemic has been the main challenge for the banking industry, which functions as financial intermediation and one of the pillars supporting economic development. The study employs the REGC (Risk Profile, Earnings, Good Corporate Governance, Capital) method to investigate the soundness level of regional development banks in eastern Indonesia during the Covid-19 Pandemic. The type of research in the study is a descriptive method with a quantitative approach. The object of this research is eight regional development banks in eastern Indonesia. The financial statements, such as the Balance Sheet and the Income Statement from 2020 to 2021, will be analyzed. The study finds that during the COVID-19 pandemic, all banks showed good soundness, reflected in composite rankings 1 and 2. Banks must improve the efficacy of their risk management and governance implementation to enable the bank to identify problems sooner and implement appropriate and faster improvements to make it more resilient in the face of crises, so the bank can keep maintaining excellent performance to support the development of eastern Indonesia, which is the main focus of national development. Keywords: Composite Ranking, Covid 19-Pandemic, REGC, Regional Development Bank, Soundness Level.